Peningkatan Hasil Belajar FPB dengan Pendekatan Contextual Teaching and Learning di Kelas V SD - Ryani, Atri Ulfa; Masniladevi, Masniladevi; Arlis, Syamsu (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aimed to describe the process, implementation, and learning outcomes of FPB by applying the Contextual Teaching and Learning (CTL) approach in the fifth grade SDN 11 Indarung, Padang City. The type of research used is classroom action research with qualitative and quantitative approaches. The subjects were teachers and fifth grade students of SDN 11 Indarung who taught 25 people. The results showed: a) the increase in the first cycle 94.7% increased to 96.4% in the second cycle, b) the implementation of aspects of the teacher in the first cycle 85.9% increased to 90.6% in the second cycle, c) aspects of implementation students in the first cycle 76.2% increased to 90.6% in the second cycle, and d) Learning outcomes in the first cycle 79.6 increased to 86.48 in the second cycle. It can be censored that the CTL approach can improve FPB learning outcomes. Keywords: Contextual Teaching and Learning (CTL), FPB